The Influence of Student Learning Motivation and Family Environment on Student Learning Outcomes - Rahmad; Keysia Vectrina Zahra; Vivid Vidyasari; Asri Karolina (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2025)
This study evaluates the influence of learning motivation and family environment on the learning outcomes of fourth-grade students at MI Al-Ishlah Palembang. This study used quantitative methods. The analysis found that learning motivation has a significant positive influence with a contribution of 64.7% to learning outcomes. The family environment also has a significant positive influence, explaining 49.7% of the variation in learning outcomes. Regression analysis showed that the combination of these two factors explained 65.7% of the variation in learning outcomes. These findings emphasize the importance of motivation and family support in improving student academic achievement.